2011
DOI: 10.1111/j.1462-2920.2011.02436.x
|View full text |Cite
|
Sign up to set email alerts
|

The protein folding challenge in psychrophiles: facts and current issues

Abstract: SummaryThe protein folding process in psychrophiles is impaired by low temperature, which exerts several physicochemical constraints, such as a decrease in the folding rate, reduced molecular diffusion rates and increased solvent viscosity, which interfere with conformational sampling. Furthermore, folding assistance is required at various folding steps according to the protein size. Recent studies in the field have provided contrasting and sometimes contradictory results, although protein folding generally ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 57 publications
1
40
0
Order By: Relevance
“…Despite this well-recognized limitation, the challenge of protein synthesis and folding in psychrophiles has been addressed only recently, mainly via proteomics and, to a lesser extent, transcriptomics [36, 62]. These approaches have produced a huge amount of data with, however, contrasted patterns of cold adaptation [43, 55, 7195].…”
Section: Protein Synthesis and Foldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this well-recognized limitation, the challenge of protein synthesis and folding in psychrophiles has been addressed only recently, mainly via proteomics and, to a lesser extent, transcriptomics [36, 62]. These approaches have produced a huge amount of data with, however, contrasted patterns of cold adaptation [43, 55, 7195].…”
Section: Protein Synthesis and Foldingmentioning
confidence: 99%
“…Indeed, proteins differentially expressed at low temperature, either cold induced or cold repressed, do not constitute a conserved set of proteins in terms of identification and expression levels in these organisms. It has been suggested that cold adaptation superimposes on preexisting cellular organization and, accordingly, that the adaptive strategies may differ between the various psychrophilic organisms [35, 62]. Nevertheless, and as far as protein synthesis and folding are concerned, some general trends have been noted.…”
Section: Protein Synthesis and Foldingmentioning
confidence: 99%
“…permanently and successfully thriving in constantly cold environments) have been recently investigated by various modern proteomic methods (for references, see Piette et al 2011b). For instance, the Antarctic bacterium P. haloplanktis grown at low temperature overexpresses enzymes involved in protein synthesis and folding and regulates its cytoplasmic redox balance as a result of improved oxygen solubility.…”
mentioning
confidence: 99%
“…Due to the high 2 activation energy, prolyl isomerization is an intrinsically slow process and is strongly temperature 3 dependent (Schmid, 2005). Accordingly, it has been suggested that prolyl isomerization strongly 4 decelerates protein folding in psychrophiles at low temperature (Piette et al, 2011a). PhTF 5 resembles EcTF in its substrate specificity but shows about tenfold lower activity towards proline-6 containing tetrapeptides (Figs.…”
Section: Accepted Articlementioning
confidence: 98%